2010
DOI: 10.1038/oby.2010.58
|View full text |Cite
|
Sign up to set email alerts
|

Hyperandrogenemia in Obese Peripubertal Girls: Correlates and Potential Etiological Determinants

Abstract: IntroductIonPolycystic ovary syndrome (PCOS) may be the most common endocrine disorder of young women, affecting ~7% of women in their reproductive years (1). Hallmarks of PCOS include ovarian hyperandrogenemia (HA) and ovulatory dysfunction (2,3). The etiology of PCOS remains unclear, but hyperinsulinemia, neuroendocrine abnormalities (e.g., exaggerated luteinizing hormone (LH) secretion), and primary abnormalities of ovarian steroidogenesis have all been proposed as causes (4-6).Manifestations of PCOS often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 30 publications
(41 reference statements)
4
39
0
Order By: Relevance
“…It has been reported that LH is the main inductor of ovarian androgen production (Knudsen et al 2010), whereas hyperinsulinemia contributes to roughly 20% of serum testosterone levels (Azziz et al 2001, Norman et al 2002, Creanga et al 2008. In humans (Tosi et al 2012) and animal MetS models (Newell-Fugate et al 2014, Wu et al 2014b, hyperinsulinemia is able to cause elevation of LH secretion with consequent hyperandrogenemia, as hypothalamic nuclei structures are intact.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that LH is the main inductor of ovarian androgen production (Knudsen et al 2010), whereas hyperinsulinemia contributes to roughly 20% of serum testosterone levels (Azziz et al 2001, Norman et al 2002, Creanga et al 2008. In humans (Tosi et al 2012) and animal MetS models (Newell-Fugate et al 2014, Wu et al 2014b, hyperinsulinemia is able to cause elevation of LH secretion with consequent hyperandrogenemia, as hypothalamic nuclei structures are intact.…”
Section: Discussionmentioning
confidence: 99%
“…Like adults with PCOS, obese girls with HA have increased levels of LH and decreased sensitivity to P 4 negative feedback (22,49). In late puberty, girls with obesity reportedly have increased frequency of pulsatile LH release compared with nonobese girls (57).…”
mentioning
confidence: 99%
“…36 The association between free testosterone and insulin resistance in the lean cohort (on correlation analysis) and the combined cohort (on regression modeling) is a relatively novel finding in adolescent girls without phenotypic features of polycystic ovary syndrome (PCOS). In female obesity and PCOS, associations between hyperinsulinism, elevated androgen, and decreased SHBG are well known, 37,38 but the relevance of androgen levels to glucose homeostasis in lean girls without PCOS has not been investigated comprehensively. Lean hyperandrogenic young women have higher measures of insulin resistance than lean normoandrogenic women, and it is possible that positive associations of androgens with measures of insulin resistance exist even when androgens are in a normal range.…”
Section: Discussionmentioning
confidence: 99%